PENGEMBANGAN MODEL BIOPSIKOSOSIAL ASUHAN KEFARMASIAN PADA KASUS PENYAKIT KRONIK: STUDI KUALITATIF TERHADAP PERSPEKTIF PASIEN PENDERITA GAGAL JANTUNG (CHF) - Risya Mulyani; Herda Ariyani; Dedi Hartanto; Muhammad Anshari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Congestive heart failure (CHF) is a disease that most often requires repeated treatment in the hospital. Self-care efforts allow patients to monitor and manage home syndrome, maximize well-being, reduce mortality and minimize avoidable hazards. Communication, collaboration, and patient access to bad information lead to ineffective treatment. The main problems in the care of pharmacy are improper and unsafe use of drugs and non-compliance with prescription drugs, one of which is a therapeutic regimen.. This study uses a phenomenological qualitative method in which researchers will explore the personal meaning related to biopsychosocial aspects that can affect the quality of care (pharmacy) according to the perspective of patients with CHF. The participants determined in this study were selected purposively from all patients with CHF who were treated at the Pharmacy Installation in Ulin Hospital Banjarmasin. Data analysis using the Interpretative Phenomenological Analysis (IPA) model. In this study, which explores personal meaning related to aspects of communication and collaboration that can affect the quality of care, according to the perspective of patients with congestive heart failure (CHF) in the biopsychosocial aspects, the result are: found 4 (four) themes related to results-based communication, qualitative data analysis obtained through in-depth interviews with 11 (eleven) participants, namely: (1) tangible; (2) responsive; (3) empathy; (4) assurance. And found 3 (three) themes related to collaboration based on the results of qualitative data analysis obtained through in-depth interviews with 11 (eleven) participants, namely: (1) effective communication; (2) trust; (3) feedback.